2020
DOI: 10.1007/s13300-020-00903-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Related Effectiveness and Cost of Liraglutide or Insulin in German Patients with Type 2 Diabetes: A 5-Year Retrospective Claims Analysis

Abstract: Introduction: Liraglutide is a glucagon-like peptide-1 analogue used to treat type 2 diabetes mellitus (T2DM). To date, limited long-term data ([ 2 years) exist comparing real-world diabetes-related effectiveness and costs for liraglutide versus insulin treatment. Methods: This retrospective claims data analysis covered the period from 1 January 2010 to 31 December 2017 and included continuously insured patients with T2DM who initiated insulin or liraglutide and had 3.5 or 5 years' follow-up data, identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Our study demonstrated that compared to insulin therapy, the higher drug acquisition, pharmacy, and outpatient costs associated with the use of GLP-1RAs are offset by reduced emergency room and inpatient costs. This is supported by recent studies from US and German adults with T2D, which reported that the use of GLP-1RAs versus insulin resulted in lower emergency room visits and inpatient admissions but higher drug acquisition costs after treatment initiation [49,50]. Therefore, evidence of the comparative cost-effectiveness of GLP-1RAs versus insulin therapy from the present study could support the formulation of healthcare reimbursement policies in real-world clinical practice.…”
Section: Table 3 Results Of Cost-effectiveness Analysis Of Glp-1ras Versus Insulin (Base-case and Sensitivity Analyses)supporting
confidence: 82%
“…Our study demonstrated that compared to insulin therapy, the higher drug acquisition, pharmacy, and outpatient costs associated with the use of GLP-1RAs are offset by reduced emergency room and inpatient costs. This is supported by recent studies from US and German adults with T2D, which reported that the use of GLP-1RAs versus insulin resulted in lower emergency room visits and inpatient admissions but higher drug acquisition costs after treatment initiation [49,50]. Therefore, evidence of the comparative cost-effectiveness of GLP-1RAs versus insulin therapy from the present study could support the formulation of healthcare reimbursement policies in real-world clinical practice.…”
Section: Table 3 Results Of Cost-effectiveness Analysis Of Glp-1ras Versus Insulin (Base-case and Sensitivity Analyses)supporting
confidence: 82%
“… 8 However, Liraglutide treatment is not associated with higher total direct healthcare costs when compared with the clinical effectiveness that is maintained for long term (up to five years), reduced incidence of diabetes and/or its related complications and improvements in health-related quality of life. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%